2017
DOI: 10.7759/cureus.1318
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Radiofrequency Ablation as an Adjunct in Treatment of Lumbar Facet Cysts

Abstract: Lumbar facet cysts are frequently found in patients with facet degeneration and segmental instability. When the facet cyst is localized in the neural foramina and lateral recess or becomes large, it can cause radiculopathy or neurogenic claudication. These symptomatic cysts are typically treated interventionally with drainage and a corticosteroid injection or attempts via overinflation to rupture the cyst; however, these procedures have a significant recurrence rate (up to 50%) and often need to be repeated or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this technique the cyst is percutaneously drained under image guidance and then cauterized along with the associated facet capsule and facet joint, where the original cyst developed. The outcomes from this study and long-term follow-up demonstrated that this technique reduces the frequency of cyst recurrence compared to simple aspiration and steroid injection or cyst rupture [26].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this technique the cyst is percutaneously drained under image guidance and then cauterized along with the associated facet capsule and facet joint, where the original cyst developed. The outcomes from this study and long-term follow-up demonstrated that this technique reduces the frequency of cyst recurrence compared to simple aspiration and steroid injection or cyst rupture [26].…”
Section: Discussionmentioning
confidence: 70%
“…A recent study described the use of targeted radiofrequency ablation to manage facet cyst [26]. In this technique the cyst is percutaneously drained under image guidance and then cauterized along with the associated facet capsule and facet joint, where the original cyst developed.…”
Section: Discussionmentioning
confidence: 99%
“…The success of RFA has been demonstrated in patients with severe spinal stenosis or pathological FJ cysts and patients who do not require surgery after examination and imaging modalities [ 35 , 36 ]. If sufficient soft tissue is coagulated, patients can experience lasting clinical relief of their symptoms and improvement in spinal motion.…”
Section: Discussionmentioning
confidence: 99%
“…This joint fluid in one or both facets is often seen on axial MRI scans or in cases with development of facet cysts. Radiofrequency thermocoagulation can be used after cyst drainage to reduce the incidence of cyst recurrence [ 19 ]. Pulsed radiofrequency has been used directly to the synovium and within large and small joints elsewhere in the body for pain control [ 20 ].…”
Section: Discussionmentioning
confidence: 99%